Comparison of manual vacuum aspiration and misoprostol in the management of incomplete abortion - Gabkika Bray Madoue; Dangar Daniel; AdoumTchari; Mahamat Chene; Khadidja Mahayedine Salah; Zakaria Brahim; Constant Naîm; Ndilbe Steve (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2016)
Background: Incomplete abortions can be managed expectantly, surgically and medically (using misoprostol). Expectant management is safe in places where women have access to information, appropriate care and follow-up; however, in isolated and poor areas women who come for help need an intervention. Objective: To compare the efficiency of manual vacuum aspiration (MVA) and misoprostol in the treatment of incomplete abortion. Patients and method: This was a prospective study over five months from March to August 2015. All patients admitted with a diagnosis of incomplete abortion were recruited into the study. Results: 308 patients with incomplete abortion were randomized into two treatment groups - MVA (done under local anaesthesia) and misoprostol (400 micrograms by the vaginal route). MVA was successfully performed for all patients. Two patients presented with anaemia. In the misoprostol group, 23 patients had vaginal bleeding, and 10 persistence of incomplete abortion. Conclusion: MVA is more effective than misoprostol with less complications in the treatment of incomplete abortion when it is done by a trained person.